Pengaruh Penatalaksanaan Gym Ball terhadap Penurunan Intensitas Nyeri Ibu Bersalin Kala I Fase Aktif - Mujiwati, Eva; Simanjuntak, Merida (Neolectura, 2024)
Edema in pregnant women occurs normally or physiologically this occurs due to the accumulation of fluid in the body tissues. It usually starts to appear in the third trimester. Edema treatment can be done by acupuncture, warm water compresses, light yoga stretching. One of them is foot massage and warm water soak mixed with kencur. This study aims to determine the effect of foot massage and warm water soak mixed with galangal on edema in third trimester pregnant women. The search strategy was carried out through Google Scholar. The research method used was literature review with a total of five articles. The results showed that there was a significant decrease after the intervention, the average range of decrease was 1-1.45 cm. By knowing the effect of foot massage and warm water soak mixed with kencur on edema in third trimester pregnant women, it is hoped that this action can be applied to pregnant women who experience edema in the third trimester.